Medieval times - Sitko, Joseph (Colorado : Chariot [production company] ; Illinois : AGC/United Learning [distributor], 1992)
Describes medieval period by taking a close look at the castle at Chepstow in South Wales
Narrator: Lois La Fond
Keywords: United Kingdom -- History -- Medieval period, 1066-1485